Cost Analysis of Physical Therapy Clinic In Thailand: The impact of the COVID-19 outbreak - Raoyrin Chanavirut; Saowanee Nakmareong; Ponlapat Yonglitthipagon; Pisamai Malila; Worawan Kamruecha (ACHSM, 2023)
Objective: The aim of the study was to identify the financial burden and compare the unit costs that Coronavirus disease 2019 (COVID-19) imposed on a physical therapy clinic that are one of the primary forms of healthcare facilities in Thailand. Design and Setting: The study was a retrospective study conducted at the physical therapy clinic, Khon Kaen University Community Outreach Center (KKUCOMOC) in Thailand. To assess the impact of the outbreak, the service unit was divided into two units: physical therapy (PT) and Thai massage (TM), and the annual report for the 2019-2021 fiscal year was analyzed as representative of before and during an outbreak. The study tool was the Handbook of Unit Cost Analysis from the Office of the Permanent Secretary. Revenue, expenses, and the number of patient visits were all gathered. The data was then analyzed and summarized using Microsoft Excel programs, and descriptive statistics were presented. Results: The COVID-19 pandemic not only reduced the number of patient visits but also the revenue. During the pandemic, the percentage of expense to the facility's revenue increased in both units. Labor, material, and capital costs were the major cost components, with labor costs accounting for the majority of direct costs. The first emerged in the 2020 fiscal year, resulting in an increase in PT's and TM's unit costs of 26.66% ($US10.24 to $US12.97) and 22.69% ($US6.92 to $US8.49), respectively. Following that, it continued to rise in both units throughout the subsequent fiscal year. As a result, at the end of the study, the unit costs of PT and TM were $US13.95 and $US9.22 respectively. Conclusions: The COVID-19 pandemic reduced the number of patient visits and revenue. Furthermore, it raised the unit cost of PT and TM to $US13.95 and $US9.22 respectively.